Механизм устранения организационного сопротивления персонала внедрению системы управления качеством - Грязева, М.С. (Економіка промисловості, 2016)
Разработан механизм устранения организационного сопротивления персонала внедрению системы управления качеством, трансформирующий протестный потенциал в созидающий на основе активного модульного управления поведением персонала посредством формирования побудительных мотивов. Сформулированы принципы мобилизации интеллектуальных активов предприятия. Обоснована когнитивная модель каузальной связи субъектов и объектов управления. Рекомендован инструментарий внедрения системы управления качеством, обеспечивающий преодоление организационного сопротивления персонала, функциональная и организационная структура механизма устранения организационного сопротивления персонала. Розроблено механізм усунення організаційного опору персоналу впровадженню системи управління якістю, який трансформує протестний потенціал утворюючий на основі активного модульного управління поведінкою персоналу шляхом формування спонукальних мотивів. Сформульовано принципи мобілізації інтелектуальних активів підприємства. Обґрунтовано когнітивну модель каузального зв'язку суб'єктів та об'єктів управління. Рекомендовано інструментарій упровадження системи управління якістю, що забезпечує подолання організаційного опору персоналу, функціональну та організаційну структуру механізму усунення організаційного опору персоналу. The mechanism of elimination of personnel organizational resistance to the introduction of the quality management system that transforms the protest potential into a creative one based on the active modular management of the personnel’ behavior by means of forming the incentive motives has been developed. The principles of mobilization of the enterprise’s intellectual assets and improvement of the controllability of the process of organizational routines modulation have been formulated. They are as follows: total quality management, group coordination and training, general quality standardization. The cognitive model of the causal relations of subjects and objects of management has been proposed. The tools for implementation of the quality management system ensuring the overcoming of personnel resistance to change, as well as the functional and organizational structure of the mechanism of elimination of personnel organizational resistance have been recommended. The advantages of the mechanism proposed are as follows: firstly, the creation of a system of balances - compensation mechanisms, incentive systems that can fully or partially balance the costs and benefits for the personnel, caused by changes in development strategy and reach compromise on key positions which cause the resistance; secondly, provision of individual and group interaction among agents hierarchical vertical of organization, the inclusion of personnel in the decision-making process regarding the reform of organizational routines and granting employees more authority on the organization of working space according to the new requirements and quality standards; and thirdly, the improvement of the quality of organization change implementation through targeted training of employees in business routines changes: professional development, coordination of allocation of professional duties and responsibilities, establishment of reasonable deadlines for the implementation of activities and improvement of the control system.